Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

the answers are in the screen shot

are you still there?

>>>???

dy/dt xy = -9
dy/dt xy = -9
xy' = -9
y' = 9/7

dx/dt xy = - 9
yx' = - 9
y(-7) = - 9
y =-9/-7
y = 9/7

I think this is right just using implicit differentiation

and chain rule

do you understand how I got my answer?

ok send me a link to your next question

austra i sent you a mail

no lol.

both are functions of time.

oh I guess so :)

d/dt( x*y=-9) = dx/dt*y + x*dy/dt =0
dy/dt = -dx/dt *y/x

can you break down the steps clearer algebraic!

it's just use of the product rule on x*y =-9
then solving algebraically for dy/dt

you do take the derivative on both sides and you do 'get 0'